Review of Timothy D. Taylor. 2001. Strange Sounds: Music, Technology, and Culture. New York: Routledge - Zak, Albin J. III (Current Musicology, 2002)
Strange Sounds is among the growing literature concerned with the interface of technology and musical practice, reception, and use (referred to in this book, as in many others, as “production” and “consumption”). More specifically, the author is concerned with the ways “that digital technology shapes the three areas that have historically been so affected by technology: music production, storage/distribution, and consumption” (15), with a particular focus on the latter two. The ability to capture sound as digital information is, of course, an outgrowth of analog sound recording, and is thus only the latest chapter in a history of technological evolution that has both shaped and been shaped by the forces of musical culture. The field of potential inquiry for such a project is vast, and from the complex of relevant topics Taylor takes up a subset focusing on “agency” and “ideologies of technology” (9), with the aim of probing the social dimensions of the music/ technology interface. What emerges is a somewhat idiosyncratic investigation that draws attention to several unlikely historical and aesthetic connections.